Parental Perceptions With Reference To Paediatric Covid-19 Vaccination: An Outpatient Department-Based Study In A Tertiary Care Hospital (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Vaccination has played a major role in preventing many deaths in children due to certain infections. Immunizing children always pose a challenge and India has overcome many barriers to vaccinate the children. Recently COVID 19 vaccination has played a key role in bringing the pandemic under control.Material and Methods: A cross-sectional study, conducted among the parents of children attending the pediatrics outpatient department of a tertiary care hospital in Chengalpattu district, during the month of May 2022 to August 2022 (post omicron peak) after obtaining approval from the Institutional Human Ethics Committee. Parents of all children under 18 years attending pediatrics outpatient department during the study period were approached and explained about the nature and purpose of the study. Children who have been vaccinated with either one or both the doses of COVID-19 vaccine were excluded from the study.Results: Majority of the children (59.1%) whose parents participated in the study were between the age of 1 month to 6 years. In our study father’s education played a significant role in deciding the vaccine acceptancy (P-value – 0.03). 96.4% of parents had good belief towards childhood vaccination and 97.8% were found to be adherent to the national immunization schedule. Almost 81.3% of the participants parents were aware of the COVID-19 symptoms in children. 89.5% of the parents reported that all the family members have completed two doses of adult COVID-19 vaccination in their household. Around 75.2% of the parents were aware of the pediatric COVID-19 vaccine availability and nearly 67.5% were willing to vaccinate their children against COVID-19. The predominant reason cited by the parents who were not willing to vaccinate their children against COVID-19 was the fear of side-effects related to vaccination (54.8%). Majority of the parents preferred intramuscular injection (59.5%) rather than intranasal vaccination (17.1%).Conclusion: This study concludes that there is a good awareness and acceptance amongst parents towards pediatric COVID-19 vaccination in our study population. This implies that the vaccination drive in children will be a huge success.